Stakeholder Relations Perspectives in Managing Nigeria’s Rising Crimes - Daniel Nwanmereni (RIRAI Publisher, 2022)
In today’s Nigerian society, crime represents a critical stakeholder. The unprecedented rise in crimes, such as, armed robbery, cultism, kidnapping, terrorism, banditry and cattle rustling has constrained the Nigerian government to introduce several crime fighting approaches. Despite government efforts, especially through State security forces, crimes have assumed a worsening dimension with increasing cases of attacks and abduction of villagers, worshippers, travellers and other settlers around Nigeria. Schools around the country are not spared, as both students and staff of different levels of educational institutions are kidnapped for ransom and sometimes killed by bandits and terrorists. Many Nigerian farmers have also been forced to abandon their farms due to incessant attacks. Not only are lives and property threatened, the Nigerian economy is also distressed by the impacts of insecurity on agriculture and the attendant hike in the prices of essential food commodities. Following the seeming inability of regular government crime fighting approaches to substantially deal with Nigeria’s rising insecurity, this paper examined the application of stakeholder relations perspectives to approach the country’s worsening insecurity. The qualitative paper combined Stakeholder and Relational Dialectics as theoretical cornerstone. It examined the impacts of some crime-yielding challenges, such as, illiteracy, unemployment, poverty, economic inequality and pseudo-social participation on the meteoric rise in crime in Nigeria. The paper recommended the application of dialogue in managing the rising militia activities and crimes. It was also recommended that beyond equipping State security formations, Nigerian government should direct attention to the conditions that breed crimes in the country.